2019
DOI: 10.1177/1350650119882834
|View full text |Cite
|
Sign up to set email alerts
|

Static and stability analysis of partial slip texture multi-lobe journal bearings

Abstract: This paper presents one-dimensional analysis of modified dynamic Reynolds equation derived for partial slip texture multi-lobe journal bearings. The novelty included in this study is the configuration of partial slip texture region on the bottom bearing lobe surface of a multi-lobe journal bearing under a constant vertical load. The nondimensional pressure and shear stress for steady-state and nondimensional pressure gradients for dynamic coefficients for each lobe with partial slip texture configuration are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Their study shows that heterogeneous slip/ no-slip region load carrying capacity and pressure distribution improve with the increase in roughness parameter. Rao et al [101] studied the variation of stiffness and damping coefficient for different slip-texture journal bearing profiles. They observed that stiffness and damping coefficient decrease with an increase in the eccentricity ratio.…”
Section: Journal Bearing With Texturementioning
confidence: 99%
See 1 more Smart Citation
“…Their study shows that heterogeneous slip/ no-slip region load carrying capacity and pressure distribution improve with the increase in roughness parameter. Rao et al [101] studied the variation of stiffness and damping coefficient for different slip-texture journal bearing profiles. They observed that stiffness and damping coefficient decrease with an increase in the eccentricity ratio.…”
Section: Journal Bearing With Texturementioning
confidence: 99%
“…• Journal bearing with slip boundary condition and random surface roughness give an improvement in load carrying capacity and maximum pressure [100]. • Partial slip and texture region significantly influence the dynamic stability of bearing [101].…”
Section: Journal Bearing With Texturementioning
confidence: 99%
“…[13][14][15][16][17][18]21] Other studies [1][2] concentrated only on the effect of slip on plain journal bearings or two-lobe bearings. [19] Also, to add to the above gaps, Recently, Das and roy [22] investigated the influence of non-Newtonian lubricant on multilobe bearings, and Rao et al [27] investigated the effect of partial slip with texturing on multilobe bearings using Newtonian fluids. Thus, to the evidence relating, no research has focused on the combined influence of non-Newtonian lubricant and wall-slip on the static and stability properties of the lemon-bearing.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that to achieve a high load-carrying capacity, a higher preload factor is required. Rao et al 10 analyzed the effect of partial-slip textures on various multi-lobe bearing configurations (2-axial grooves, 2-lobe, 3-lobe, and offset journal bearings) and predicted that among them, two-lobe showed an improvement in the load-carrying capacity and linear stability.…”
Section: Introductionmentioning
confidence: 99%